2020
DOI: 10.1093/nar/gkaa146
|View full text |Cite
|
Sign up to set email alerts
|

G-quadruplex ligands mediate downregulation of DUX4 expression

Abstract: Abnormal DUX4 expression in skeletal muscles plays a key role in facioscapulohumeral muscular dystrophy (FSHD) pathogenesis, although the molecular mechanisms regulating DUX4 expression are not fully defined. Using bioinformatic analysis of the genomic DUX4 locus, we have identified a number of putative G-quadruplexes (GQs) forming sequences. Their presence was confirmed in synthetic oligonucleotiode sequences derived from the enhancer, promoter and transcript of DUX4 through circular dichroism and nuclear mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 80 publications
0
16
0
Order By: Relevance
“…Clinical management involving physiotherapies, vision and hearing aids, orthopedic interventions, pain and fatigue management or surgical scapular fixation has shown some clinical benefit and improved the quality of life for FSHD patients ( 49 , 50 ). Since aberrant expression of the DUX4 gene has been extensively reported as the main causative factor of FSHD ( 9–14 , 20 ), pre-clinical strategies silencing DUX4 expression have shown promise for FSHD treatment ( 20 , 22 , 24 , 29 , 41 , 51–53 ). Among antisense approaches, those targeting the pLAM region of DUX4 3′UTR, including ours, have provided the best down-regulatory effect ( 20 , 24 , 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical management involving physiotherapies, vision and hearing aids, orthopedic interventions, pain and fatigue management or surgical scapular fixation has shown some clinical benefit and improved the quality of life for FSHD patients ( 49 , 50 ). Since aberrant expression of the DUX4 gene has been extensively reported as the main causative factor of FSHD ( 9–14 , 20 ), pre-clinical strategies silencing DUX4 expression have shown promise for FSHD treatment ( 20 , 22 , 24 , 29 , 41 , 51–53 ). Among antisense approaches, those targeting the pLAM region of DUX4 3′UTR, including ours, have provided the best down-regulatory effect ( 20 , 24 , 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Berberine, an alkaloid that can be extracted from a variety of plants and previously shown to bind G-quadruplex DNA and RNA structures [39,40], was used to inhibit DUX4 expression. A reduction of DUX4 mRNA was observed in FSHD cells but not in vivo after a local injection of an adeno associated virus-DUX4 (AAV-DUX4) followed by repeated intraperitoneal injections of Berberine [38]. However, in vivo, a reduction of the DUX4 protein was observed.…”
Section: Upstream Approach: Targeting Dux4 Transcriptionmentioning
confidence: 98%
“…Recently, G-quadruplex (GQ) structures, which are formed in DNA or RNA that are rich in guanine through the formation of Hoogsten hydrogen bonds between bases (for review see [37]), were identified within the enhancer, promoter, and DUX4 transcripts [38]. Berberine, an alkaloid that can be extracted from a variety of plants and previously shown to bind G-quadruplex DNA and RNA structures [39,40], was used to inhibit DUX4 expression.…”
Section: Upstream Approach: Targeting Dux4 Transcriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyaluronic acid has been reported as a signaling molecule in the mechanism of DUX4-induced molecular pathologies, which is indicative of its potential to be a therapeutic target [ 118 ]. Several G-quadruplex-forming sequences were discovered in the DUX4 locus, and berberine, a G-quadruplexes ligand, later proved to suppress DUX4 expression in patient-derived myoblasts and increase muscle strength in mouse models [ 119 ]. Although the picture is unlikely to be complete and a greater discovery of DUX4 expression factors are needed so that researchers could establish a more comprehensive pathogenic mechanism, these findings can still serve as novel therapeutic targets to treat FSHD.…”
Section: Facioscapulohumeral Muscular Dystrophy (Fshd)mentioning
confidence: 99%